Towards an improved geological interpretation of airborne electromagnetic data: a case study from the Cuxhaven tunnel valley and its Neogene host sediments (northwest Germany). Issue 2 (30th December 2014) - Steinmetz, D.; Winsemann, J.; Brandes, C.; Siemon, B.; Ullmann, A.; Wiederhold, H.; Meyer, U.
Abstract: Airborne electromagnetics (AEM) is an effective technique for geophysical investigations of the shallow subsurface and has successfully been applied in various geological settings to analyse the depositional architecture of sedimentary systems for groundwater and environmental purposes. However, interpretation of AEM data is often restricted to 1D inversion results imaged on resistivity maps and vertical resistivity sections. The integration of geophysical data based on AEM surveys with geological data is often missing and this deficiency can lead to uncertainties in the interpretation process. The aim of this study is to provide an improved methodology for the interpretation of AEM data and the construction of more realistic 3D geological subsurface models. This is achieved by the development of an integrated workflow and 3D modelling approaches based on combining different geophysical and geological data sets (frequency-domain helicopter-borne electromagnetic data (HFEM), time-domain helicopter-borne electromagnetic data (HTEM), three 2D reflection seismic sections and 488 borehole logs). We used 1D inversion results gained from both HFEM and HTEM surveys and applied a 3D resistivity gridding procedure based on geostatistical analyses and interpolation techniques to create continuous 3D resistivity grids. Subsequently, geological interpretations have been performed by combining with, and validation against, borehole and reflection seismic data. To verify the modelling results and to identify uncertainties of AEM inversions and interpretation, we compared the apparent resistivity values of the constructed 3D geological subsurface models with those of AEM field measurements. Our methodology is applied to a test site near Cuxhaven, northwest Germany, where Neogene sediments are incised by a Pleistocene tunnel valley. The Neogene succession is subdivided by four unconformities and consists of fine-grained shelf to marginal marine deposits. At the end of the Miocene an incised valley was formed and filled with Pliocene delta deposits, probably indicating a palaeo-course of the River Weser or Elbe. The Middle Pleistocene (Elsterian) tunnel valley is up to 350 m deep, 0.8–2 km wide, and incised into the Neogene succession. The unconsolidated fill of the Late Miocene to Pliocene incised valley probably formed a preferred pathway for the Pleistocene meltwater flows, favouring the incision. Based on the 3D AEM resistivity model the tunnel-valley fills could be imaged in high detail. They consist of a complex sedimentary succession with alternating fine- and coarse-grained Elsterian meltwater deposits, overlain by glaciolacustrine (Lauenburg Clay Complex) and marine Holsteinian interglacial deposits. The applied approaches and results show a reliable methodology, especially for future investigations of similar geological settings. The 3D resistivity models clearly allow a distinction to be made between different lithologies and enables the detection of major bounding surfaces and architectural elements.